Cancer trends in Eastern India: Retrospective hospital-based cancer registry data analysis - Pandey, Avinash; Raj, Shraddha; Madhawi, Richa; Devi, Seema; Singh, Rajesh Kumar (South Asian Journal of Cancer, 2019)
Background: Trends of cancer cases vary across several hospital-based cancer registries (HBCRs). There is a paucity of demographic data to evaluate trends of cancer in Eastern India. Aim: The aim of this study is to evaluate trends and pattern of cancer cases with respect to time from HBCR from Bihar. Objectives: The objective of this study is to evaluate the numbers of consecutive patients registered with eight most common type of cancer in our HBCR in Regional Cancer Centre, Bihar, and to evaluate trends of cancer cases registered with respect to time. Materials and Methods: Demographic profile of consecutive cancer patients registered from January 2014 to December 2016 (3 years) in HBCR was obtained. Patients diagnosed with common malignancies including head-and-neck cancer, gallbladder, breast, cervix, ovary, esophagus, stomach, hematolymphoid, and colorectal were analyzed. Frequency distribution, crosstabs, and line diagram were used to evaluate the trends of these common cancers with respect to time. Results: Sixty-six thousand and twenty-nine consecutive patients were registered between 2014 and 2016. Carcinoma gallbladder was the most common malignancy (21%), followed by head-and-neck cancer (19%) and breast cancer (15%). Median age at the diagnosis was 55 years for carcinoma gallbladder while 53 years and 46 years for head-and-neck and breast cancer, respectively. Male-to-female ratio was 0.6 for carcinoma gallbladder and 1.8 for head-and-neck cancer. A number of gallbladder and head-and-neck cancer registered increased by 36% (between 2014 and 2015) and 5% (between 2015 and 2016) and 24% (between 2014 and 2015) and 4% (between 2015 and 2016), respectively. Carcinoma breast and cervix showed decreasing trend with fall in registration up to 13% (between 2015 and 2016) and 27% (between 2015 and 2016), respectively. Conclusion: Carcinoma gallbladder is the most common cancer in Bihar. Head-and-neck cancer and carcinoma gallbladder are increasing while breast and cervical cancers are decreasing with respect to time.
Keywords: Bihar; cancer registry; cancer trend